The Difference Between Exercise-Induced Autonomic and Fitness Changes Measured After 12 and 20 Weeks of Medium-to-High Intensity Military Training. Issue 9 (September 2016) - Grant, Catharina C.; Mongwe, Lot; Janse van Rensburg, Dina C.; Fletcher, Lizelle; Wood, Paola S.; Terblanche, Etrisia; du Toit, Peet J.
Abstract : Abstract: Grant, CC, Mongwe, L, Janse van Rensburg, DC, Fletcher, L, Wood, PS, Terblanche, E, and du Toit, PJ. The difference between exercise-induced autonomic and fitness changes measured after 12 and 20 weeks of medium-to-high intensity military training. J Strength Cond Res 30(9): 2453–2459, 2016—The aim of this study was to compare the physical fitness, based on VO2 max and exercise-induced cardiac autonomic changes, measured by heart rate variability (HRV) of 12 weeks with 20 weeks of training in the South African National Defence Force. Recruits ( n = 154) participated in a medium-to-high intensity exercise intervention (daily energy expenditure: 8, 485 kJ·d −1 ). The significant effect on VO2 max between weeks 1 and 12 (48.57, SD = 9.25 vs. 53.36, SD = 7.21] did not continue during weeks 12–20 (53.36, SD = 7.21 vs. 53.87, SD = 7.87). No changes in the supine low frequency (LF)/high frequency (HF) (0.48, SD = 0.51 vs. 0.41, SD = 0.64) or the standing LF/HF (4.02, SD = 5.14 vs. 3.91, SD = 5.28), an indicator of autonomic balance and a possible indicator of overtraining syndrome, suggests that overtraining did not take place during weeks 12–20. This was confirmed with further decreases in supine and standing heart rate. However, the power of the vagal-induced variability continued to increase after 12 weeks. Increased vagal influence without concurrent change in autonomic balance may be interpreted as decreased sympathetic cardiac control. It is important to note that although no fitness changes were detected, positive cardiac autonomic conditioning did continue between weeks 12 and 20, as measured by increased vagal-induced HRV and decreased sympathetic influence on cardiac control. Results may be extrapolated to training in the normal population/athletes after a medium-to-high intensity exercise program, as this intervention was a closely monitored and standardized exercise program.